Animal Spirits, Margin Requirements, and Stock Price Volatility. - Kupiec, Paul H; Sharpe, Steven A (Journal of Finance, 1991)
A simple overlapping generations model is used to characterize the effects of initial margin requirements in the volatility of risky asset prices. Investors are assumed to exhibit heterogenous preferences for risk-bearing, the distribution of which evolves stochastically across generations. This framework is used to show that imposing a binding initial marginal requirement may either increase or decrease stock price volatility, depending upon the microeconomic structure behind fluctuations in economywide average risk-bearing propensity. The ambiguous effect on volatility similarly arises when the source of heterogeneity is noise trader beliefs.